An examination of flexible work arrangements, work-family conflict, and organizational outcomes / Jacob Ongaki - Ongaki, Jacob (Accounting Research Institute (ARI), 2020)
The purpose of this quantitative study was to examine whether or not a relationship existed between employees' use of flexible working arrangements (such as flexible work schedules and telecommuting) and organizational outcomes (such as turnover intentions and job satisfaction outcome variables) holding work-family conflict and family-work conflict as covariate variables. The ANCOVA and Kruskal-Wallis technique was utilized in a survey data of 237 employees who utilized flexible work arrangements in the state of Texas. The ANCOVA and Kruskal-Wallis results revealed non-statistically significant results employees use flexible work options (such as flexible work schedules and telecommuting) to reduce work-family conflict and family-work conflict (P > 0.05). The investigation found no statistical relations for the use of flexible work arrangements and outcome variables (such as work-family conflict, job performance, and turnover intentions). This issue would benefit researchers and organizational management together with human resources to recognize employees' challenges (work-family conflict and family-work conflict) and further investigate circumstances to reduce employees' negative feelings of job satisfaction and turnover intentions. Effective policies would likely improve and support employees' morale and boost organizational competitiveness in a global economy. Also, a study is needed to investigate employees' perceptions regarding the outcome variable if the flexible work arrangement options were reversed/rescinded in their organization.